Molecular Docking Studies of Curcumin Analogues against SARS-CoV-2 Spike Protein - Nogueira, Jéssica R.; Verza, Flávia A.; Nishimura, Felipe; Das, Umashankar; Caruso, Ícaro P. [UNESP]; Fachin, Ana L.; Dimmock, Jonathan R.; Marins, Mozart (Sociedade Brasileira de Quimica (SBQ), 2021)
Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) is the etiologic agent of the current pandemic of coronavirus disease 2019 (COVID-19) that has inflicted the loss of thousands of lives worldwide. The coronavirus surface spike (S) glycoprotein is a class I fusion with a S1 domain which is attached to the human angiotensin converting enzyme 2 (ACE2) receptor, and a S2 domain which enables fusion with the host cell membrane and internalization of the virus. Curcumin has been suggested as a potential drug to control inflammation and as a potential inhibitor of S protein, but its therapeutic effects are hampered by poor bioavailability. We performed a molecular docking and dynamic study using 94 curcumin analogues designed to have improved metabolic stability against the SARS-CoV-2 spike protein and compared their affinity with curcumin and other potential inhibitors. The docking analysis suggested that the S2 domain is the main target of these compounds and compound 2606 displayed a higher binding affinity (-9.6 kcal mol-1) than curcumin (-6.8 kcal mol-1) and the Food and Drug Administration (FDA) approved drug hydroxychloroquine (-6.3 kcal mol-1). Further additional validation in vitro and in vivo of these compounds against SARS-CoV-2 may provide insights into the development of a drug that prevents virus entry into host cells.
Keywords: Coronavirus; COVID-19; Curcumin; Molecular docking; SARS